2021
DOI: 10.21831/cp.v40i3.40466
|View full text |Cite
|
Sign up to set email alerts
|

The analysis on teaching skills and learning effectiveness of internship students

Abstract: The effectiveness of implementing Pengenalan Lapangan Persekolahan, a new program of introduction to teaching internship, for PE students, is still questionable, starting from its impact on teaching skills, learning effectiveness, and students' teaching load. Meanwhile, this point is significant in Kurikulum Merdeka Belajar Kampus Merdeka (MBKM). For this reason, this analytic study will criticize MBKM by providing evidence of the effectiveness of existing internships in the form of teaching skills, learning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…The instrument that the researcher used consists of two forms; the first is in the form of giving HOTS-based questions. Moreover, the second is a questionnaire using Formative Class Evaluation (FCE) adopted by (Tuasikal et al, 2021). The researcher used the FCE questionnaire sheet to determine the effectiveness of the PE learning process that has been carried out in terms of students' opinions.…”
Section: Research Instrumentmentioning
confidence: 99%
“…The instrument that the researcher used consists of two forms; the first is in the form of giving HOTS-based questions. Moreover, the second is a questionnaire using Formative Class Evaluation (FCE) adopted by (Tuasikal et al, 2021). The researcher used the FCE questionnaire sheet to determine the effectiveness of the PE learning process that has been carried out in terms of students' opinions.…”
Section: Research Instrumentmentioning
confidence: 99%
“…In contrast, the results of previous studies show that institutional challenges are the biggest. (Tuasikal et al, 2021). Teachers can utilize technology, such as interactive or applicative learning software (Jones et al, 2021), to increase student interaction and engagement.…”
Section: Creativity In Implementing Merdeka Curriculummentioning
confidence: 99%
“…Table 3 also showed that the standard deviation value is high, which means that the students' competence differed with high variances. Therefore, students need to work hard in the future lectures by focusing on essential learning materials (Tuasikal, Hartoto, Prakoso, Kartiko, & Hariyanto, 2021). These findings are important for lecturers because they can be used as a basis in determining strategies used to prepare learning plans.…”
Section: The Students' Entry-level Competenciesmentioning
confidence: 99%